Oral Anticoagulants in Orthopaedic Surgeries Comparison of Rivaroxaban and Standard-of-Care - Khot, Dr. Sanjay; Kamra, Dr. Sunil Kant (International Journal of Innovative Research in Medical Science, 2018)
Background: Venous thromboembolic (VTE), deep vein thrombosis (DVT) and pulmonary embolism (PE), cause significant morbidity, mortality and healthcare costs. Direct oral anticoagulant which has been demonstrated in clinical trials, anaesthetists need to be careful of how to minimize the risks of bleeding complications when treating patients who are taking an anticoagulant. Rivaroxaban, non-vitamin K antagonist direct oral anticoagulants (DOACs), was shown to be more effective regimens for the prevention of VTE after orthopaedic surgery. Aims and objectives: To look for the influence of timing of the first thromboprophylactic dose and clinical outcomes in patients undergoing orthopaedic surgery Method: Patients aged ≥18 years, with planned orthopaedic surgery or fracture-related orthopaedic surgery and in whom thromboprophylaxis has been indicated. Out of 324 patients selected for the study 164 received rivaroxaban 10 mg once daily and 160 received standard-of-care (SOC) pharmacological prophylaxis. Incidences of symptomatic thromboembolic events and bleeding events were analysed. Bleeding events and thromboembolic events recorded and calculated for the rivaroxaban and SOC groups. Results: Overall major bleeding events observed in rivaroxaban group was 9 (5.49%) was much lower than the SOC group which was 13 (8.13%).The percentage of patients using mechanical methods alongside pharmacological thromboprophylaxis was slightly higher in the rivaroxaban as compared to SOC groups ( 64% and 55%). Overall thromboembolic effect was lower in rivaroxaban as compared to SOC group. Conclusion: Comparison of rivaroxaban & SOC shows the effectiveness and safety of rivaroxaban in patients undergoing major orthopedic surgery in clinical practice. Major bleeding events & thromboembolic with rivaroxaban were less as compared to SOC group.